Prognostic significance of neutrophil–lymphocyte ratio and carbohydrate antigen 19-9 in patients with gallbladder carcinoma. Issue 8 (February 2019) - Liu, Fei; Hu, Hai-Jie; Ma, Wen-Jie; Yang, Qin; Wang, Jun-Ke; Li, Fu-Yu
Abstract : Abstract: The neutrophil–lymphocyte ratio (NLR) is an immune response-related indicator and it is associated with poor prognosis of various cancers. The carbohydrate antigen19-9 (CA19-9) is a tumor-associated antigen and it has prognostic relevance in gallbladder carcinoma (GBC). We aimed to analyze whether preoperative NLR and serum CA19-9 were associated with outcomes of GBC patients after surgery with curative intent. Between January 2010 and May 2015, 90 resectable GBC patients who underwent curative surgery in our institution were included. All final diagnoses were confirmed by pathologic examination. The demographics, clinical, and histopathology data were analyzed. The Cox regression proportional hazard model and Kaplan–Meier method were used to assess prognostic factors. The cutoff values of 4.33 and 250.90 U/mL were defined as high NLR and high CA19-9, respectively. The univariate analyses showed that TNM stage, lymph node metastasis, the degree of tumor differentiation, margin status, combined hepatectomy, CA19-9, NLR, and PNI were all associated with overall survival ( P  < .05). According to the multivariable analysis, NLR (hazard ratio (HR) 3.840, 95% confidence interval (95% CI): 2.122–6.947, P  < .001), CA19-9 (HR 2.230, 95% CI: 1.297–3.835, P  = .004), TNM stage (HR 3.864, 95% CI: 1.819–8.207, P  < .001), lymph node metastasis (HR 1.679, 95% CI: 1.005–2.805, P  = .048), and margin status (HR 1.873, 95% CI: 1.063–3.300, P  = .030) were independent prognostic factors. The median survival time in low NLR and CA19-9 group was better than high NLR and CA19-9 group ( P  < .05). The preoperative NLR and serum CA19-9 are associated with prognosis of patients with GBC. High NLR and high CA19-9 were predictors of poor long-term outcome among patients with GBC undergoing curative surgery.